The Causal Mechanism of Financial Education : Evidence from Mediation Analysis - Carpena, Fenella (World Bank, Washington, DC, 2018)
This paper uses a field experiment in India with multiple financial education treatments to investigate the causal mechanisms between financial education and financial behavior. Focusing on the mediating role of financial literacy, the paper proposes a broader definition of financial knowledge that includes three dimensions: numeracy skills, financial awareness, and attitudes toward personal finance. The analysis then employs causal mediation analysis to investigate the proportion of the treatment effect that can be attributed to these three channels. Strikingly, numeracy does not mediate any effects of financial education on household outcomes. For simple financial actions such as budgeting, both awareness and attitudes serve as critical pathways, while for more complex financial activities such as opening a savings account, attitudes play a more prominent role. These findings underscore the importance of changing perceptions about financial products and services as a vital mechanism for the success of financial education.